Biomedicine or Holistic Medicine for Treating Mentally Ill Patients? A Philosophical and Economical Analysis - Søren Ventegodt; Isack Kandel; Joav Merrick (The Scientific World Journal)
Today we have two scientific medical traditions, two schools or treatment systems: holistic medicine and biomedicine. The two traditions are based on two very different philosophical positions: subjectivistic and objectivistic. The philosopher Buber taught us that you can say I-Thou or I-It, holding the other person as a subject or an object. These two fundamentally different attitudes seem to characterize the difference in world view and patient approach in the two schools, one coming from psychoanalysis and the old, holistic tradition of Hippocratic medicine. Holistic medicine during the last decade has developed its philosophical positions and is today an independent, medical system seemingly capable of curing mentally ill patients at the cost of a few thousand Euros with no side effects and with lasting value for the patient. The problem is that very few studies have tested the effect of holistic medicine on mentally ill patients. Another problem is that the effect of holistic medicine must be documented in a way that respects this school's philosophical integrity, allowing for subjective assessment of patient benefit and using the patient as his/her own control, as placebo control cannot be used in placebo-only treatment. As the existing data are strongly in favor of using holistic medicine, which seems to be safer, more efficient, and cheaper, it is recommended that clinical holistic medicine also be used as treatment for mental illness. More research and funding is needed to develop scientific holistic medicine.